Evaluation of waste plastic and waste cooking oil as a potential alternative fuel in diesel engine - Amit Kumar; Harveer Singh Pali; Manoj Kumar (Next Energy)
The generation of plastic waste and waste cooking oil is a serious environmental concern because of worldwide waste disposal issues. At the same time, increasing demand and contemporary geopolitics make fossil fuels a significant worldwide problem. As a result, there has been an increase in demand for alternate fuel for CI engines. To overcome these twin problems can be addressed by converting waste into liquid fuels. This research explores an intriguing area by mixing waste cooking oil biodiesel and waste plastic oil to create a mixture that remarkably seems like the physico-chemical properties of diesel fuel in a society that is looking for sustainable alternatives. So, in this investigation, a ternary fuel blend of Petro-diesel, waste cooking oil biodiesel (WCOB), and waste plastic oil (WPO) was used in the diesel engine. To enhance the properties of fuel, combustion, emission, and performance parameters of diesel engines, a ternary blend of B20P20D60 was employed in the CI engine as an alternative fuel. In the ternary fuel blends, WCOB, WPO, and diesel content were 20%, 20%, and 60%, respectively. The results were compared with conventional diesel fuel, showing that the ternary fuel blend B20P20D60 has an improved brake thermal efficiency of up to 1.71% at 80% loading and reduced emissions (HC, CO, NOx) compared to conventional diesel. Because of this, the ternary blends have significant potential for use in diesel engines.